Observation of multiphonon transverse wobbling in 133Ba - K. Rojeeta Devi (Elsevier, 2021)
The low-lying negative parity states in the 133Ba nucleus have been investigated using the 124Sn(13C, 4nγ)133Ba reaction at Elab = 48 MeV. With the addition of new γ-transitions, nω=0,1,2 wobbling bands were identified in this nucleus. The angular correlations and linear polarization measurements have been performed to confirm the spin and parity of the states. Predominant E2 character was obtained for the inter-linking ΔI=1 transitions between the successive phonon (Δnω=1) wobbling bands. The transverse nature of the wobbling bands is concluded on the basis of observed decreasing behavior of the wobbling frequency with increasing spin. The quasiparticle triaxial rotor model calculations are found to be in agreement with the experimentally determined wobbling frequency and the transition probability ratios. This letter reports the first observation of transverse wobbling mode associated with a hole-like quasiparticle.